ATRIAL FIBRILLATION IN HEMATO-ONCOLOGIC PATIENTS: EPIDEMIOLOGY, MECHANISMS, AND CLINICAL IMPLICATIONS - Jakub Tarczykowski; Szymon Stupnicki; Michał Woźniak; Natalia Kwaśniewska; Mikołaj Zakryś; Katarzyna Anna Zakryś; Mateusz Szot; Aleksandra Oparcik (International Journal of Innovative Technologies in Social Science, 2025)
Background: Atrial fibrillation (AF) is a common cardiac arrhythmia that affects approximately 2% of the population. In the population of patients with hematological neoplasms, there is an increased risk of developing atrial fibrillation. Despite growing evidence linking AF with hematological malignancies, current research rarely differentiates individual malignancies, leaving significant gaps in understanding disease-specific mechanisms. Objective: The aim of this study is to demonstrate the correlation between an increased risk of atrial fibrillation in hemato-oncological patients, to present the mechanisms underlying the onset of AF in these patients, and to outline the challenges associated with arrhythmia management in this group of patients Materials and Methods: The article is based on scientific literature sourced from PubMed, SpringerLink and Google Scholar. Results: Patients with hematological malignancies have a markedly increased risk of developing atrial fibrillation compared to cancer-free patients. Multiple factors may explain this linking; for example, anemia, electrolyte disruption, cytokine-mediated atrial remodeling, radiation exposure, and side effects of various therapies, including anthracyclines, CAR-T, or tyrosine kinase-inhibitors. AF in this population is often complicated by higher rates of bleeding, thromboembolic events, and treatment interactions. Conclusions: Atrial fibrillation represents a growing clinical challenge in hematology and oncology, requiring individualized treatment and close multidisciplinary collaboration, especially between cardiologists and oncologists. Current data suggest the need for disease-specific testing, improved risk stratification models, and the identification of predictive biomarkers. A more profound understanding of the mechanisms linking AF and hematologic malignancies could ultimately improve prevention, diagnosis, and tailored therapeutic strategies.